Effects of Dietary Guanidinoacetic Acid on the Performance, Rumen Fermentation, Metabolism, and Meat of Confined Steers - Giraldi G.C.* (2024)
© 2024 by the authors.With the increase in population, it is increasingly necessary to produce food more efficiently. This has expanded the market for additives, which are products that directly (nutritional effect) or indirectly (effect on animal health) favor productivity. Guanidinoacetic acid (GAA) is a natural precursor of creatine. It acts as an energy reserve in skeletal muscle. In addition to being a compound with more significant bioavailability, it is more thermally stable and less expensive than creatine. Therefore, this study aimed to determine whether adding GAA to the cattle diet would alter the meat’s composition and fatty acid profile. We used 24 Holstein cattle males (409 ± 5.6 kg), approximately 15 months old, and separated them into four homogeneous groups, one being the control group and three groups with various dosages of GAA in the diets (3.3; 6.6, and 9.9 g/animal/day), for an experimental period of 60 days. Blood, rumen fluid, and animal weighing were performed at three points (days 1, 30, and 60), and daily feed consumption was measured. Steers fed with GAA (9.9 g/d) showed a 16.9% increase in average daily gain (ADG) compared to the control group. These same animals (T-9.9 group) fed with GAA showed a 20% increase in fed efficiency compared to the control group. Lower leukocyte, lymphocyte, and granulocyte counts and lower cholesterol levels were observed in animals that consumed 6.6 g and 9.9 g/d GAA compared to the control group. Animals from the T-6.6 and T-9.9 groups showed 30% and 27.6% reduced bacterial activity in the rumen compared to the control group, respectively. Steers from the T-6.6 and T-9.9 groups fed with GAA showed a 20% and 37% increase in short-chain fatty acids (SCFAs) compared to the control group, respectively. A higher concentration of acetic, propionic, and butyric acids in the ruminal fluid of cattle T-9.9 group was observed at day 60. The two highest doses of GAA showed lower fat levels in the meat, just as the cattle that received 9.9 g/d showed higher levels of total polyunsaturated fatty acids. Complementary data results draw attention to the dose of 9.9 g/d GAA in cattle diets, as anti-inflammatory action can be seen and combined with a higher concentration of SCFAs, consequently increases weight gain. We concluded that consuming this GAA increases the concentration of some unsaturated fatty acids (omegas) in the meat, which adds quality to the product for the consumer.